Oxidative Degradation of Amoxicillin in Aqueous Solution by Thermally Activated Persulfate - Juanjuan Zhao; Yujiao Sun; Fachao Wu; Minjian Shi; Xurui Liu (Journal of Chemistry)
Antibiotic residues and antibiotic resistance genes (ARGs) pose a great threat to public health and food security via the horizontal transfer in the food production chain. Oxidative degradation of amoxicillin (AMO) in aqueous solution by thermally activated persulfate (TAP) was investigated. The AMO degradation followed a pseudo-first-order kinetic model at all tested conditions. The pseudo-first-order rate constants of AMO degradation well-fitted the Arrhenius equation when the reaction temperature ranged from 35°C to 60°C, with the apparent activate energy of 126.9 kJ·mol−1. High reaction temperature, high initial persulfate concentration, low pH, high Cl− concentration, and humic acid (HA) concentration increased the AMO degradation efficiency. The EPR test demonstrated that both ·OH and SO4·− were generated in the TAP system, and the radical scavenging test identified that the predominant reactive radical species were SO4·− in aqueous solution without adjusting the solution pH. In groundwater and drinking water, AMO degradation suggested that TAP could be a reliable technology for water remediation contaminated by AMO in practice.